Structural Manipulation of Eicosanoid Receptors and Cellular Signaling. (2007) - Brink, Charles
Abstract : Eicosanoids are lipid mediators derived from the metabolism of arachidonic acid. These agents are locally released and activate different cell membrane receptors, and the latter are part of the G-protein coupled receptor family. While activation of eicosanoid receptors is associated with a wide variety of actions, there is limited information concerning the structural components of the eicosanoid receptors. To date, our understanding of the eicosanoid ligand-receptor binding interaction has been based on the rhodopsin template model. While receptors in the same family do share a common architecture, there are amino acid residues in the membrane binding pocket that play a key role in ligand recognition as well as the diversity observed in the cellular signaling. In order to understand the eicosanoid receptor binding interaction, attention must be focused on both the nature of the endogenous ligands as well as the template G-protein model that has been proposed. The data derived from chemical alterations in the endogenous ligands, together with the mutagenesis studies involving the structural modifications of the eicosanoid receptors, have suggested a working model of the eicosanoid receptors. However, the data also document various nuances in the receptor structure associated with ligand binding as well as a number of differences that will require further investigation.